A Decision-Analytic Approach to Addressing the Evidence About Football and Chronic Traumatic Encephalopathy - Brand, Kevin P.; Finkel, Adam M. (Seminars in Neurology, 2019)
Doubts can be raised about almost any assertion that a particular exposure can lead to an increase in a given adverse health effect. Even some of the most well-accepted causal associations in public health, such as that linking cigarette smoking to increased lung cancer risk, have intriguing research questions remaining to be answered. The inquiry whether an exposure causes a disease is never wholly a yes/no question but ought to follow from an appraisal of the weight of evidence supporting the positive conclusion in light of any coherent theories casting doubt on this evidence and the data supporting these. More importantly, such an appraisal cannot be made sensibly without considering the relative consequences to public health and economic welfare of specific actions based on unwarranted credulity (false positives) versus unwarranted skepticism (false negatives). Here we appraise the weight of evidence for the premise that repeated head impacts (RHIs) in professional football can increase the incidence of chronic traumatic encephalopathy (CTE) and, in turn, cause a variety of cognitive and behavioral symptoms. We first dismiss four logical fallacies that should not affect the appraisal of the weight of evidence. We then examine four alternative hypotheses in which RHI is not associated with CTE or symptoms (or both), and we conclude that the chances are small that the RHI→ CTE→ symptoms link is coincidental or artifactual. In particular, we observe that there are many specific interventions for which, even under a skeptical appraisal of the weight of evidence, the costs of a false positive are smaller than the false negative costs of refusing to intervene.
Keywords: CTE; epidemiology; weight of evidence; uncertainty; risk management